Berberine in fish nutrition: Impact on hepatoenteric health, antioxidative and immune status - Wang, Lei; Sagada, Gladstone; Wang, Chenyang; Gao, Chang; Wang, Bin; Shao, Qingjun; Yan, Yunzhi (Frontiers in Marine Science, 2022)
Berberine, an isoquinoline alkaloid found in some traditional medicinal plants, such as Berberis vulgaris and Coptis Chinensis, has been considered as an effective drug in treating obesity, hypertension, type-2 diabetes, hyperlipidemia, and gout in humans and animals. It currently has certain applications in fish nutrition and health, mainly because it has strong biological and pharmacological properties, such as antioxidative, anti-inflammation, antidiarrheal, analgesic, antimicrobial, anticancer, hepatoprotective, and lipid- and glucose-lowering properties. Recent studies revealed that berberine supplementation in different fish diets could alleviate liver pathological changes, intestinal histological and microbiota alterations caused by high lipid and carbohydrate diets, as well as improve growth performance, antioxidative and immune status, and stress resistance ability of fish. However, the beneficial effects of berberine vary with fish species, basal diet, feeding modes, supplementation level, and etc. This review highlights the bioavailability and toxicity of berberine, and its mechanisms in lipid and glucose metabolism, antioxidation, anti-inflammation, and protection of intestinal health, as well as the other findings on supplementing berberine in the fish diet. Moreover, this review provides future perspectives on berberine application in fish nutrition and health.